Multi-dimensional impact of captopril modification on human serum albumin - Ghosh, Amrita; Jani, Vinod; Sonavane, Uddhavesh; Naphade, Anvi N.; Joshi, Rajendra; Kulkarni, Mahesh J.; Giri, Ashok P. (International Journal of Biological Macromolecules, 2024)
Captopril is a thiol drug, widely used for the management of hypertension and cardiovascular diseases. Reactive thiols are found to covalently modify the cysteines of plasma proteins and affect their structure and function. Human serum albumin (HSA) is prone to undergo modification by various low molecular weight compounds, including drugs. Cysteine34 (Cys34) in HSA has a free thiol group with antioxidant properties, considered to be the most redox-sensitive amino acid in plasma. Through mass-spectrometric analysis, we demonstrate for the first time that captopril forms a disulfide adduct at Cys34 residue and increases the protease susceptibility of HSA to trypsin. As evidenced by our biophysical and electron microscopy studies, HSA undergoes structural alteration, aggregation and morphological changes when treated with different captopril concentrations. Molecular dynamics studies further revealed the regions of secondary structural changes in HSA due to disulfide adduct formation by captopril at Cys34. It also elucidated the residues involved in the noncovalent interactions with captopril. It is envisaged that structural change in HSA may influence the efficacy of drug delivery as well as its own biological function. These findings may thus provide significant insights into the field of pharmacology intriguing further investigation into the effects of long-term captopril treatment.
Keywords: Captopril; Electron microscopy; Human serum albumin; Mass spectrometry; Molecular dynamic simulation; Spectrophotometry